EMBRYONIC MORTALITY IN COBB BROILER BREEDER STRAIN WITH THREE EGG WEIGHT AND STORAGE PERIODS AT FOUR PRODUCTION PHASES - H. M. Ishaq; M. Akram; M. E. Baber; A. S. Jatoi; A. W. Sahota; K. Javed; S. Mehmood; J. Hussain; F. Husnain (Journal of Animal and Plant Sciences, 2014)
The present study was conducted at a commercial hatchery with the objective to evaluate the effects of egg weight and storage period on embryonic mortality (early, mid and late) during incubation of fertile eggs from Cobb broiler breeder strain during 4 production phases(pre-peak; 25-28, peak; 29-36, post-peak; 37-52 and terminal; 53-56th weeks of age), categorized into 3 egg weights (small, medium and large subjected to change in each production phase) and maintained at 3 different storage periods (1, 4- and 7-days)and replicated 6 times. A total 93312 fertile eggs (pre-peak: 11664, peak: 23328, post-peak: 46656 and terminal: 11664) in 4 production phases were incubated in a commercial hatchery. The data were analyzed by ANOVA technique under randomized complete block design in 4×3×3 factorial arrangement and means were compared by using DMR Test. The results of the present study showed that the egg weight categories significantly (p<0.05) affected embryonic mortality in all the production phases. The highest early and late embryonic mortality was observed in small egg weight category followed by that of medium and large egg weight categories. Higher mid embryonic mortality was observed in small and large egg weight categories than in medium ones.  Storage period was also significantly (p<0.05) affected embryonic mortality in all production phases. Higher early, mid and late -embryonic mortality was observed in seven days storage than those of four and one day storage. As for as interaction between egg weight categories and storage periods is concerned, the highest (p<0.05) early embryonic mortality was observed in seven days storage with small egg weight category in all production phases, while, the lowest was in one day storage with all the egg weight categories in all the production phases. It may be concluded from the present study that large egg weight category with 1 or 4 days storage period resulted in lower embryonic mortality leading to higher hatchability.
Keywords: Broiler breeder strain; early; mid and late embryonic mortality; production phases